Mild hypothermia facilitates the long-term survival of newborn cells in the dentate gyrus after traumatic brain injury by diminishing a pro-apoptotic microenvironment. (29th October 2016) - Chen, Chong; Ma, Tie-Zhu; Wang, Li-Na; Wang, Jing-Jing; Tu, Yue; Zhao, Ming-Liang; Zhang, Sai; Sun, Hong-Tao; Li, Xiao-Hong
Highlights: Mild hypothermia facilitated long-term survival of newborn cells in DG post TBI. Mild hypothermia promoted maturation of newborn cells in DG post TBI. Mild hypothermia improved pro-apoptosis microenvironment in the hippocampus after TBI. Mild hypothermia improved TBI-induced cognitive impairment. Abstract: Although previous research has demonstrated that traumatic brain injury (TBI) accelerates the proliferation of neural stem cells in dentate gyrus of the hippocampus, most of these newborn cells undergo apoptosis in a traumatic microenvironment. Thus, promoting the long-term survival of newborn cells during neurogenesis is a compelling goal for the treatment of TBI. In this study, we investigated whether mild hypothermia (MHT) therapy, which mitigates the multiple secondary injury cascades of TBI, enhances the survival of newborn cells. SD rats were subjected to unilateral fluid percussion injury and received MHT therapy for 4 h (33.5 °C). Bromodeoxyuridine (BrdU) was administered to label the mitotic cells. Spatial learning and memory were evaluated with the Morris water maze test. Brain sections were immunostained with antibodies against BrdU, DCX (a neuroblast marker) or NeuN (a mature neuron marker). The apoptosis levels in the dentate gyrus were examined with antibodies against the apoptotic proteins FAS, FASL, Bcl-2 and cleaved caspase 3. The results indicated that MHT could significantly prevent TBI-induced cognitive impairments. At 1 week after injury, the density of BrdU-immunoreactive cells significantly increased in both TBI and TBI + MHT rats. At 4 weeks after injury, the density of BrdU-positive cells further increased in TBI + MHT rats, whereas the density declined in the TBI rats. The density of DCX-positive cells in SGZ of the hippocampus at 1 week after injury in the TBI + MHT rats was significantly greater than in the TBI rats. Moreover, the density of NeuN-positive cells in the subgranular zone at 4 weeks after injury and in the granule cell layer at 7 weeks after injury was significantly increased in the TBI + MHT rats. The TBI + MHT rats displayed a lower level of apoptosis in the dentate gyrus compared with the TBI rats. These data indicate that TBI could only facilitate a burst of proliferation and short-term survival of newborn cells, whereas TBI + MHT could facilitate long-term survival and maturation of newborn cells through diminishing pro-apoptotic microenvironment. These results suggest that MHT-mediated neurogenesis may have an important therapeutic potential for the endogenous repair of TBI.